Entropy and Negentropy in Translation - Samain, Didier (Swiss Journal of Educational Research, 2018)
The author bases his paper on his experience as a translator and historian and focuses on the specificity of the concepts in moral sciences and hence of their translation or rewording. Using descriptive metaconcepts (such as cognitive truncation and boundary effect), he shows that translation implies both information gains and losses of it. Though not denying the interest of culturalist analyzes, he thus proposes a more historical and formal approach, getting rid of common places about ‘original’ and ‘copy’ in favour of seeing the rewording mechanisms as metadiscursive processes. Besides the analysis emphasizes the ambiguity of the idea of «translation», as it is illustrated by the Quinian notion of radical translation.